Efficacy of Topical Application of Chum Salmon (Oncorhynchus keta) Skin-derived Collagen Extracts in Improving Oral Traumatic Ulcer Healing - Dian Mulawarmanti; Syamsulina Revianti; Endah Wahjuningsih (Wolters Kluwer Medknow Publications, 2024)
Background: Traumatic ulcer is a wound on the oral mucosa that often causes pain and impaired eating function. Healing of these wounds takes a long time and can interfere with an individual's daily activities. One therapeutic approach that is being developed is the use of topical application of chum salmon skin-derived collagen extract. Collagen is the main component of the extracellular matrix and plays a major role in wound healing. The skin of chum salmon (Oncorhynchus keta) contains collagen that is effective for the treatment of wounds. Aim: The aim of this study was to evaluate the effectiveness of topical applications of chum salmon (O. keta) skin-derived collagen extracts in improving the healing of traumatic ulcers through analysis of neutrophil and macrophage numbers and collagen density. Materials and Methods: Twenty-four male Wistar rats were randomly divided into four groups consisting of six rats each. The labial mucosa of the lower lips of the rats was injured with heated amalgam stoppers to create oral traumatic ulcers. Group 1 was a control group; in Groups 2, 3, and 4, 25%, 50%, and 75% of collagen extracts from chum salmon (O. keta) skin were applied topically once a day for 7 days, respectively. The neutrophil and macrophage numbers were observed by hematoxylin and eosin staining. Masson's Trichrome staining was used to analyze the collagen density. Data were analyzed using one-way analysis of variance and continued with post hoc least significant difference tests. Significance is considered if P < 0.05. Results: The oral traumatic ulcers gradually healed until day 7. The number of neutrophils and macrophages was significantly decreased in the treatment groups, and collagen density was increased, compared to the control group (P < 0.05). The decrease of neutrophil and macrophage numbers occurred significantly with the increased collagen extract concentrations (P < 0.05). Collagen density also increased significantly with the increased collagen extract concentrations (P < 0.05). Conclusion: Topical applications of chum salmon (O. keta) skin-derived collagen extracts accelerate the healing process of oral traumatic ulcers by decreasing neutrophil and macrophage numbers and increasing collagen density.